Field diary: the author as a protagonist - Scheinvar, Estela; Lívia do Nascimento, Maria (Revista Pesquisas e Práticas Psicossociais, 2017)
This article presents some analyses of intervention practices carried out in schools and tutorial councils, taking two references as methodological basis: 1) the institutional analysis proposed by René Lourau and Georges Lapassade, which problematizes the naturalization of institutional relations and their heterogeneity; 2) Michel Foucault’s concept of “event”, which calls into question the analysis of relations sustained in patterns of truth. To follow the course of the analyses, we take a powerful auxiliary: the field diary as a tool that allows the strangeness of ways of codifying practices. Keywords: Field Diary; Institutional Analysis; Event; Michel Foucault.